First record of the isopod Idotea hectica (Pallas, 1772) (Idoteidae) and of the brachyuran crab Matuta victor (Fabricius, 1781) (Matutidae) in the Hellenic waters - KONDYLATOS, GERASIMOS; CORSINI-FOKA, MARIA; PERAKIS, EMMANOUIL (Mediterranean Marine Science, 2018)
The presence and the establishment of Idotea hectica is reported for the first time in the Hellenic seas on the basis of three adult specimens and a juvenile collected from Posidonia oceanica meadows close to the main town of Rhodes Island, Aegean Sea. Common and contrasting characters between this and other species of the genera Idotea and Pentidotea are briefly discussed. Furthermore, following a westward expansion along the eastern Mediterranean coasts, Matuta victor was discovered for the first time in Hellenic waters on the basis of a single specimen from the northeast of Rhodes Island.